Exploring the potential of fermented papaya as a functional ingredient for sourdough bread: a study on fermentation time and quality of sourdough donuts - Anisa Mutamima; Ahmad Fadli; Indra Purnama; Yelmida Azis; Muhammad Syafiq Izzuddin (Universitas Lancang Kuning, 2023)
Sourdough bread is known to have health benefits due to its fermentation process using lactic acid and wild yeast. It can improve the taste, texture, shelf life, and nutritional content of bread as a functional food. In this study, sourdough was made from fermented papaya with varying fermentation times of 4, 5, and 6 days. The substrate was fed five times to strengthen the sourdough, resulting in a robust enough mixture to develop the dough. The resulting sourdough was used to create sourdough bread with a 30% sourdough concentration. The fermentation time impacted the quality of the sourdough, with results showing that sourdough became increasingly active as fermentation time progressed. The best sourdough was obtained from a six-day fermentation period, with a pH of 3.60 and a total plate count of 1.70 × 104 CFU/ml. The best donuts were produced using the sourdough that had been fermented for six days, with an almost perfect score of 3.9 out of 4 for all aspects, including color, aroma, taste, and texture. Using this sourdough resulted in a significantly longer shelf life; no mold appeared until the eighth day of storage at room temperature. The moisture content of the donuts was measured at 4.57%. This study demonstrates the potential benefits of using sourdough made from fermented papaya to improve the quality and shelf life of sourdough bread while also providing potential health benefits.